A Bibliometric Analysis of Personal Protective Equipment and COVID-19 Researches - Zhang, Yu; Hu, Man; Wang, Junwu; Wang, Pingchuan; Shi, Pengzhi; Zhao, Wenjie; Liu, Xin; Peng, Qing; Meng, Bo; Feng, Xinmin; Zhang, Liang (Frontiers in Public Health, 2022)
COVID-19, which occurred at the end of December 2019, has evolved into a global public health threat and affects every aspect of human life. COVID-19’s high infectivity and mortality prompt governments and the scientific community to respond quickly to the pandemic outbreak. The application of personal protective equipment (PPE) is of great significance in overcoming the epidemic situation. Since the discovery of SARS-CoV-2, bibliometric analysis has been widely used in many aspects of the COVID-19 epidemic. Although there are many reported studies about PPE and COVID-19, there is no study about the bibliometric analysis of these studies. The citation can be used as an indicator of the scientific influence of an article in its field. The purpose of this study was to track the research trends and latest hotspots of COVID-19 in PPE by means of bibliometrics and visualization maps.